Wzrost gospodarczy i uwarunkowania : stan i perspektywy rozwoju Republiki Białorusi - Połonik, Stepan S.; Połonik, Lena S. (Economic Growth and Investment : State and Prospects Development of the Republic of Belarus, 2008)
In this article the socio-economic development conditions of the Republic of Belarus in years 2006 - 2010 are considered. The author is paying special attention to analysis of the investment program, taking into account that the investment market in Belarus will be determined to a considerable degree by the surge of foreign direct investments. From this reason the main issue being analyzed by the author is the evaluation of the foreign direct investments’ use effectiveness and its influence on raising economic growth rate of Belarus.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 161-167